2005
DOI: 10.1007/s11064-005-8510-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Second Pathophysiological Stress in Prevention of Delayed Neuronal Death in the Hippocampal CA1 Region

Abstract: In ischemic tolerance experiment, when we applied 5-min ischemia 2 days before 30-min ischemia, we achieved a remarkable (95.8%) survival of CA1 neurons. However, when we applied 5-min ischemia itself, without following lethal ischemia, we found out 45.8% degeneration of neurons in the CA1. This means that salvage of 40% CA1 neurons from postischemic degeneration was initiated by the second pathophysiological stress. These findings encouraged us to hypothesize that the second pathophysiological stress used 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 67 publications
4
53
0
Order By: Relevance
“…It has also been reported that systemic 3-NP administration produces oxidized proteins in the striatum and cortex as well as massive loss Fontaine 2000). Researchers also confirmed 3-NP-induced lesions and oxidative damage in hippocampus (Rodríguez-Martínez et al 2004;Silva et al 2007;Karanian et al 2006;Burda et al 2005). Turan and coworkers reported that chemical preconditioning with 3-NP reduces infarct size via a mechanism that may involve increased bioavailability of NO and decreased ONOOformation (Turan et al 2006).…”
Section: Discussionmentioning
confidence: 78%
“…It has also been reported that systemic 3-NP administration produces oxidized proteins in the striatum and cortex as well as massive loss Fontaine 2000). Researchers also confirmed 3-NP-induced lesions and oxidative damage in hippocampus (Rodríguez-Martínez et al 2004;Silva et al 2007;Karanian et al 2006;Burda et al 2005). Turan and coworkers reported that chemical preconditioning with 3-NP reduces infarct size via a mechanism that may involve increased bioavailability of NO and decreased ONOOformation (Turan et al 2006).…”
Section: Discussionmentioning
confidence: 78%
“…Process of apoptosis-like delayed neuronal death manifesting practically 3 days after ischemia can be reversed by sublethal stress stimulus, delayed, protein synthesis dependent, postconditioning, used 2 days after ischemia (Burda et al 2005Danielisova et al 2006Danielisova et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prevention of inhibition of translation does not assure survival of CA1 neurons (Burda et al 2003). But endogenous defense mechanism known as ischemic tolerance inevitably needs recovery of protein synthesis (Burda et al 2005(Burda et al , 2006.…”
Section: Discussionmentioning
confidence: 99%